The Effect Of Circuit Training On Increasing The Endurance Of Futsal Players In Extracurricular Activities (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
This study aimed to determine the effect of circuit training on improving the endurance of futsal extracurricular participants at Al-Khairaat 1 Palu Junior High School. Endurance is an essential physical component in futsal because the sport requires continuous high-intensity movement, rapid transitions, and sustained physical performance throughout the match. However, many junior high school futsal players still demonstrate relatively low endurance levels, resulting in decreased playing performance during training and competition. Therefore, an effective and structured training method is needed to improve students’ physical endurance. This study employed an experimental method using a one-group pretest–posttest design. The sample consisted of 14 futsal extracurricular participants selected through a total sampling technique. The research instrument used was the Bleep Test to measure participants’ endurance abilities before and after the implementation of circuit training. Data analysis was conducted using the Kolmogorov–Smirnov normality test and paired sample t-test at a significance level of 0.05. The results of the normality test showed that the pretest and posttest data were normally distributed, with significance values of 0.969 and 0.420, respectively (p > 0.05). Descriptive statistical analysis revealed an increase in the average endurance score from 31.60 in the pretest to 38.38 in the posttest. Furthermore, the paired sample t-test produced a t-value of 16.263 with a significance value of 0.000 (p < 0.05), indicating a significant improvement after the treatment. Therefore, it can be concluded that circuit training significantly improves the endurance abilities of futsal extracurricular participants.